Spatial variation and determinants of inappropriate complementary feeding practice and its effect on the undernutrition of infants and young children aged 6 to 23 months in Ethiopia by using the Ethiopian Mini-demographic and health survey, 2019: spatial and multilevel analysis - Derseh, Nebiyu Mekonnen; Shewaye, Daniel Alayu; Agimas, Muluken Chanie; Alemayehu, Meron Asmamaw; Aragaw, Fantu Mamo (Frontiers in Public Health, 2023)
Background: Inappropriate complementary feeding practice (IACFP) is a major public health issue in Ethiopia, which usually results in stunting and an intergenerational cycle problem. Therefore, the aim of this study was to explore the spatial patterns and determinants of IACFPs and their effects on the undernutrition of infants and young children (IYC) in Ethiopia. Methods: This was a nationwide community-based survey study among 1,463 mothers of IYC aged 6–23 months in Ethiopia. The global spatial autocorrelation was assessed using the global Moran’s-I to evaluate the spatial clustering of IACFPs. Significant clusters with high and low rates of IACFPs were explored. A multilevel mixed-effect logistic regression with cluster-level random effects was fitted to identify determinants of IACFPs with an AOR and 95% CI. Results: The prevalence of IACFP was 90.22% (95% CI: 88.58–91.64). The spatial pattern was clustered across regions (Global Moran’s I = 0.63, Z-score = 12.77, P-value ≤ 0.001). Clusters with a high rate of IACFP were detected in southern, northwestern, and eastern Ethiopia. Individual and community-level variables accounted for 63% of IACFP variation. Mothers with no education were 3.97 times (AOR = 3.97; 95% CI: 1.64–9.60) more likely to have IACFPs than those with higher education. The poorest HHs had 4.80 times the odds of having IACFPs as the richest HHs (AOR = 4.80, 95% CI: 1.23–18.71). The odds of having IACFPs were 2.18 times (AOR = 2.18; 95% CI: 1.28–3.72) higher among babies with no postnatal checkup. Non-breastfed IYC were 2.8 times (AOR = 2.80; 95% CI: 1.29–6.10) more likely to have IACFP when compared with breastfed ones. IYC with the inadequate introduction of solid, semi-solid, and soft foods, inadequate minimum dietary diversity, and inadequate minimum acceptable diet were more likely to have wasting, underweight, and stunting. Conclusion: This study showed the prevalence of IACFPs was very high, which had an effect on undernutrition and showed spatial variation in Ethiopia. Therefore, the government of Ethiopia and stakeholders should focus on women with no education and the poorest HHs, encourage PNC checkups, and encourage breastfeeding in the hotspot areas to minimize IPCFPs in Ethiopia.